2014
DOI: 10.3109/14756366.2014.913035
|View full text |Cite
|
Sign up to set email alerts
|

Implication of novel thiazolo-thiophene derivative (MCD-KV-10) for management of asthma

Abstract: Context: Asthma is multifaceted disease where many targets contribute towards its development and progression. Among these, adenosine receptor subtypes play a major role. Objective: MCD-KV-10, a novel thiazolo-thiophene was designed and evaluated pre-clinically for its implication in management of asthma. Materials and methods: This compound showed good affinity and selectivity towards A 2A /A 3 adenosine receptor (AR) subtypes. Furthermore, MCD-KV-10 was evaluated for in vitro lipoxygenase inhibition activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In in vitro assays, when using compound 4 at a concentration of 100 µg/mL, inhibition of the enzyme 5-LOX was observed at approximately 57%. As with other thiophene derivatives with anti-inflammatory activity, compound 4 presents methyl, ester, and amine groups in its structure [ 45 ].…”
Section: The Role Of Thiophene Derivatives In Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…In in vitro assays, when using compound 4 at a concentration of 100 µg/mL, inhibition of the enzyme 5-LOX was observed at approximately 57%. As with other thiophene derivatives with anti-inflammatory activity, compound 4 presents methyl, ester, and amine groups in its structure [ 45 ].…”
Section: The Role Of Thiophene Derivatives In Inflammationmentioning
confidence: 99%
“…Patil et al [ 45 ] evaluated new thiazolo-thiophene derivatives in an asthma model, and found that compound 4 ( Figure 2 ) was able to significantly reduce the levels of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) observed in bronchoalveolar lavage.…”
Section: The Role Of Thiophene Derivatives In Inflammationmentioning
confidence: 99%
“…Thiophenes have various biological activities, including anti-microbial (Nasr et al, 2014), anti-asthma (Patil et al, 2014), anti-rheumatic (Sherif and Hosny, 2014), anti-inflammatory (Bailey et al, 1988), and anti-cancer activities (Ghorab et al, 2014;Said and Elshihawy, 2014); (Yang et al, 2014). Naturally occurring polythiophenes such as terthiophenes, in which thiophenes are attached through α-positions next to the sulfur atoms, are commonly found in plants of the family Asteraceae (Compositae) (Hudson et al, 1994) and have been proven to possess several biological activities (Ciofalo and Table 2 Cytotoxic analysis of the various compounds from the n-hexane fraction and cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…There is an urgent need for new therapeutics that are more effective and less toxic than conventional treatments used to treat infectious diseases, including leishmaniasis [ 25 ]. Thiophenes derivatives are known for their therapeutic applications and have shown promising results to treat different types of cancer, degenerative diseases, HIV, and malaria [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Thus, we evaluated the anti-leishmania activity and selectivity of nine thiophene derivatives against L. major , and potential MOA was elucidated for our best candidate, 5D .…”
Section: Discussionmentioning
confidence: 99%